Synthesis and in vitro testing of a pyropheophorbide-a-fullerene hexakis adduct immunoconjugate for photodynamic therapy - Rancan, Fiorenza; Helmreich, Matthias; Mölich, Andreas; Ermilov, Eugeny; Jux, Norbert; Röder, Beate; Hirsch, Andreas; Böhm, Fritz (Bioconjugate Chemistry, 2007)
The employment of carriers to enhance drug selectivity is one of the strategies to increase the efficacy and reduce the side effects of antitumor therapy. The concept of a modular carrier system (MCS) was developed to construct a complex drug having a high efficacy and selectivity. An MCS employs diverse units or modules: beside the therapeutic unit, an addressing unit (e.g., an antibody) serves to direct the drug to its target, and a multiplying unit has the role of increasing the number of biological active moieties the system can carry. In this paper, we report on the synthesis of a modular carrier system in which the role of multiplying unit is given to a [5:1]-fullerene hexakis adduct. This fullerene hexaadduct has five malonate spacers which can bind two therapeutic units (the photosensitizer pyropheophorbide-a) each, for a total of ten, and a longer malonate spacer which serves for the conjugation to the addressing unit, the monoclonal antibody rituximab. Confocal microscopy studies using Epstein-Barr virus-transformed B-lymphocytes and Jurkat cells showed that the antibody conjugate conserves the affinity for its receptor (CD20) and its selectivity toward CD20 positive B-lymphocytes. On the contrary, the antibody-free complex did not show any bounding or intracellular uptake. © 2007 American Chemical Society.